Knowledge and practice of standard precautions among nursing students - Khoo, Cicely Yen Wee (Universiti Malaysia Sarawak (UNIMAS), 2010)
During clinical training, lack of clinical experiences and skills predispose nursing students to higher risk of occupational exposure. Compliance of standard precautions among nursing students is important in protecting them from occupational exposure. The objective of this study was to assess the knowledge and practice of standard precautions among nursing students. This study was using quantitative method which used a 27 item self-administered questionnaire. The target group consisted of 65 UNIMAS undergraduate nursing students who already had clinical attachment experience. Data from the questionnaire was analyzed by using Statistical Package for Social Sciences (SPSS) version 17.0. In this study, overall level of knowledge among UNIMAS nursing students was found low as no respondents scored at or above equivalent of 80% of the maximum score and knowledge mean score achieved by respondents was relatively low (4.80 out of 10.0). Highest score was attained for knowledge of hand hygiene (87.7%) whereas low scores were achieved for knowledge about disinfection and sterilization management (6.2%) and basic concepts of standard precautions (16.9%). Overall level of practice of standard precautions was unacceptable as only 50.8% of the respondents exhibited good practice of standard precautions. Example of good practices were discard blood and soiled dressings into clinical wastes (86.2%), discard used needles into sharp bin immediately (78.5%) and wear gloves when doing peripheral vascular access i 3 procedures (78.5%) every time during clinical posting. Nursing students were found to have poor practice in: wearing goggles (87.7%), calling for cleaner (72.3%) and changing of gloves in between patient care (64.6%) every time in the clinical setting. There were no significant differences among nursing students of different year of study in their level of knowledge and practice of standard precautions (p>0.05). Level of knowledge was not the significant predictor of level of practice of standard precautions among nursing students. There are other factors that account for poor practice of standard precautions. In conclusion, it is imperative that continuous reinforcement on standard precautions’ concepts should be implemented throughout the education training to improve knowledge and practice of standard precautions.